2014
DOI: 10.1097/ico.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Pathologic Myopia and Dry Eye Syndrome?

Abstract: Patients with pathologic myopia have lower TBUT scores and higher OSDI scores when compared with healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…[ 15 ] Clinically, the changes in the anterior corneal surface as the eyeball elongates in myopia may contribute to increase the likelihood of developing dryness. [ 35 37 38 39 ] In conclusion, noninvasive ocular surface examinations using Keratograph 4 showed a low NIBUT in healthy participants with refractive error which could be indicative of DES. Although it would have been interesting to examine the relationship between the refractive error and development of DES, the present data need to be supported by a further study of larger population.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…[ 15 ] Clinically, the changes in the anterior corneal surface as the eyeball elongates in myopia may contribute to increase the likelihood of developing dryness. [ 35 37 38 39 ] In conclusion, noninvasive ocular surface examinations using Keratograph 4 showed a low NIBUT in healthy participants with refractive error which could be indicative of DES. Although it would have been interesting to examine the relationship between the refractive error and development of DES, the present data need to be supported by a further study of larger population.…”
Section: Resultsmentioning
confidence: 80%
“…[ 32 33 34 ] Moreover, very few studies have shown evidence that refractive errors could contribute to the development of DES in young individuals. [ 35 36 ] The aim of this study was to examine the prevalence of DES among young Saudi females in relation to the refraction error. Relying on NIBUT and TMH, the current study shows that both myopic and hyperopic individuals have significantly reduced NIBUT values of <10 s which is indicative of dryness in 61% of the participants although the TMH values were in normal range.…”
Section: Resultsmentioning
confidence: 99%
“…3 Yet, several studies have shown the alteration of anterior segment parameters as axial length (AL) increases. [4][5][6][7] More specifically, it was reported that lower corneal hysteresis and corneal resistance factor are significantly associated with longer AL 6 and that mean keratometry readings and anterior chamber depth are also higher in myopic eyes. 4 Tear break-up time was found to be briefer in pathological myopia, 5 whereas whiteto-white corneal diameter was found to be shorter in moderate to high myopia than in low myopia.…”
mentioning
confidence: 98%
“…[4][5][6][7] More specifically, it was reported that lower corneal hysteresis and corneal resistance factor are significantly associated with longer AL 6 and that mean keratometry readings and anterior chamber depth are also higher in myopic eyes. 4 Tear break-up time was found to be briefer in pathological myopia, 5 whereas whiteto-white corneal diameter was found to be shorter in moderate to high myopia than in low myopia. 7 Various methods are available for measuring the individual thickness of preocular tear film, corneal layers, and anterior sclera, although anterior segment optical coherence tomography (AS-OCT) can provide data regarding all those parameters.…”
mentioning
confidence: 99%
“…In our cohort, this is unlikely to be the case; modern contact lens materials generally offer high oxygen permeability, thus minimizing the likelihood of corneal oedema. Nevertheless, light scatter is also reported to increase in individuals with corneal surface disturbances caused by ‘dry eye’ or superficial punctuate keratitis [ 25 ] which are likely to be more prevalent amongst contact lens wearers and/or myopes [ 26 ]. Further, wearing a contact lens during the light scatter test can, in itself, adversely affect the results [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%